Immediate and long-term results of the use of balloon angioplasty with stenting in the treatment of renal graft arterial stenosis - A. V. Shabunin; P. A. Drozdov; V. A. Tsurkan; I. V. Nesterenko; D. A. Makeev; O. S. Zhuravel; S. A. Astapovich; I. A. Zyablikov (Трансплантология (Москва), 2023)
Aim. To assess the safety and efficacy of percutaneous transluminal balloon angioplasty with stenting for renal graft artery stenosis. Material and methods. From June 2018 to December 2022, 344 kidney transplants from a deceased donor were performed at the surgical clinic of City Clinical Hospital n.a. S.P. Botkin. The study group consisted of 220 men (63.9%) and 124 women (36.1%). The mean age was 46.46±11.74 (19–73) years. With a mean follow-up period of 20.05 (1-54) months, stenosis of the renal graft artery was diagnosed in 4 patients (1.16%). The mean time from transplantation to the diagnosis of stenosis was 4 (1–9) months. In addition, we diagnosed the development of this complication in 4 kidney transplant recipients operated in other centers. The mean time from transplantation to the diagnosis of stenosis in these patients was 103.25 (12–221) months. Thus, we have the experience in the treatment of renal transplant arterial strictures in 8 recipients: 4 men (50%) and 4 women (50%). The mean age was 48.25±11.97 (27–60) years. Stenosis was manifested by renal graft dysfunction with a progressive increase in urea and creatinine in 6 patients (75%), by arterial hypertension in 2 patients (25%). The mean, level of creatinine at the time of diagnosing stenosis was 290.75 (157–494) µmol/L, glomerular filtration rate was 22.87±12.19 (8–41) ml/min/1.73m2 . Results. In the early postoperative period, 1 complication was recorded in the form of pulsating hematoma of the common femoral artery, which required surgical intervention (complication class IIIA according to Clavien-Dindo). The mean hospital postoperative bed-days made 5.22 (4-8). The mean follow-up time was 22.75±7.4 (14–33) months. All recipients were alive throughout the whole follow-up period. In 7 of 8 recipients (87.5%), the graft was functioning, in 1 patient a progressive graft dysfunction was noted, for which chronic hemodialysis was started. Mean creatinine in recipients with a functioning graft was 156.71±33.4 (123–200) µmol/L; mean glomerular filtration rate was 41.57 ml/min/1.73m2 . Conclusions. Percutaneous transluminal balloon angioplasty with stenting is a safe and effective minimally invasive technique and should be considered as the operation of choice in the development of renal graft artery stenosis.